Vermicomposting of sewage sludge by lumbricus rubellus using spent mushroom compost as feed material: effect on concentration of heavy metals - Abu Bakar, A.; Mahmood, N.Z.; da Silva, J.A.T.; Abdullah, N.; Jamaludin, A.A. (2011)
Vermicomposting of sewage sludge (SS) using spent mushroom compost from Pleurotus sajor-caju as feed material was conducted to determine the effect on the concentration of heavy metals, namely Cr, Cd, Pb, Cu, and Zn. Previous studies have reported the feasibility of brandling worms, Eisenia foetida, for vermicomposting SS, whereas we conducted vermicomposting by employing red worms, Lumbricus rubellus, with a combination of different percentages of SS and spent mushroom compost (SMC) for 70 days subsequent to 21 days of precomposting. The vermicompost produced in treatments with a low percentage of SS were fine in texture, dark in colour and odourless in contrast to the initial physical characteristics. Results indicate that growth in earthworm numbers and biomass gain was maximum at 25 : 75 (T D) of SS : SMC compared to other treatments with 5 and 8- fold increases, respectively. The heavy metals contained in vermicompost were 0.25 â¼ 11.57-fold higher than the initial concentration due to mineralization and excretion of non-accumulated heavy metals existent in the earthworms' gut, which were present prior to treatments. Even so, the concentration was below the limits set by EU and US biosolid compost standards and safe to be utilized as a biofertilizer and soil conditioner. Â© The Korean Society for Biotechnology and Bioengineering and Springer 2011.